Os programas governamentais de incentivo à primeira infância no município de São Pedro do Sul e seus efeitos para a vida de crianças com deficiência - Farinha, Janessa Ebling (2024)
The following research was conducted within the Graduate Program in Education at the Federal University of Santa Maria, under Research Line 3: Special Education, Inclusion, and Difference, and within the GEPEIN Research Group. Investing in childhood is contributing to the future of society, thinking about that, two government programs were established to promote early childhood development: Better Early Childhood Program (Programa Primeira Infância Melhor/PIM), launched in 2005 in the state of Rio Grande do Sul and implemented exclusively within the state, and the Happy Child Program (Criança Feliz), initiated by the Federal Government in 2016 and implemented nationwide. Both programs aim to foster the comprehensive development of children in early childhood—spanning birth to six years old—and include prenatal support. Their primary focus is on families in socially vulnerable situations and those with children with disabilities. Program interventions are carried out through home visits, during which activities are designed to stimulate children’s development. It was through an experience within these programs in the municipality of São Pedro do Sul that we sought to analyze the result of the interventions of the Happy Child and Better Early Childhood Programs for the lives of children with disabilities. Employing a qualitative approach, the research included a documentary analysis of program data systems and legal frameworks, as well as semi-structured interviews with participating families and program professionals who were involved from 2005 to 2024. The findings highlight the importance of a cohesive and well-functioning public policy framework. Achieving optimal outcomes requires all program components to operate in harmony. Challenges related to legislation, management, political dynamics, or program personnel can significantly hinder childhood development, with immediate and long-term negative effects.